FUNDRAISING BERBASIS ZIS: STRATEGI INKONVENSIONAL MENDANAI PENDIDIKAN ISLAM - Fahrurrozi Fahrurrozi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
The study was done based on the importance of relief found for quality Islamic education process. The problem of this study was how to get the donation from Zakat, Infak, and Sedekah (ZIS) Organization for quality Islamic education process. Based on this problem, the objective of the study was to explore Rumah Zakat donation performance for formal education process “Sekolah Juara”. The quantitative analysis technique through balanced scorecard approach was used to to analyze the education donation. The result of the study showed that Rumah Zakat performance at staffing, performance development, and network is continously influence to public education performance, donation service, and accountability. Futhrmore, these performances influence society confident and gain of ZIS which is improved day to day. Moreover, these factors also influence the utilization of donation to held “Sekolah Juara” formal education program.